Genetic evaluation and classification of hard-leaf Cymbidium orchids based on DNA barcoding markers - Nguyen, Truong Giang; Pham, Phuong Thao; Huynh, Van Biet; Huynh, Huu Duc (Vietnam Journal of Biotechnology, 2026)
The hard-leaf Cymbidium orchid group comprises several species within the genus Cymbidium, including Cymbidium finlaysonianum, Cymbidium aloifolium, Cymbidium bicolor, and Cymbidium atropurpureum, which are adapted to tropical and subtropical climates. These native Vietnamese orchids have high economic value and are currently overexploited in the wild. To conserve and utilize these genetic resources, 19 samples of hard-leaf Cymbidium orchids from various regions were analyzed and genetically evaluated using DNA barcoding markers. The analysis of two chloroplast gene regions (rbcL and matK) and one nuclear gene region (ITS2) revealed the sizes of each gene region: rbcL (680-715 bp), matK (760-762 bp), and ITS2 (453 bp). Comparing the DNA sequences of these regions among the samples showed both conservation and diversity within and between species, with conserved sites (678/715, 744/762, 228/453), variable sites (37/715, 18/762, 225/453), Pi (36/715, 11/762, 191/453), and InDels (35/715, 2/762, 0/453). Phylogenetic analysis indicated that the matK gene could clearly distinguish four species; however, the rbcL gene could not differentiate between C. aloifolium and C. atropurpureum. The ITS2 region displayed high intraspecific variation but was insufficient for species discrimination. Combining rbcL and matK regions provided both intra-species diversity insights and effective species discrimination. These findings demonstrate that DNA barcoding markers are useful for species identification and assessing genetic diversity among the four hard-leaf Cymbidium orchids. They also highlight some limitations of using the ITS2 region for species identification in some instances.